Feasibility of treating hearing loss to prevent dementia in MCI: Results of the face to face and remote interventions in the Treating Auditory impairment and Cognition Trial (TACT). (31st December 2021) - Gonzalez, Sergi Costafreda; Bamiou, Doris‐Eva; Lewis, Glyn; Livingston, Gill; Omar, Rumana; Pavlou, Menelaos; Proctor, Danielle; Schilder, Anne
Abstract: Background: Age‐related hearing loss is an independent and potent risk factor for dementia. There is observational evidence that hearing aid use may mitigate deterioration in cognitive performance and could prevent dementia, but experimental evidence is lacking. A trial on whether treating hearing loss reduces the risk of dementia may not be feasible because people often do not access or use hearing aids even when prescribed. We designed the Treating Auditory impairment and Cognition Trial (TACT) as a manual‐based preventative intervention, promoting and supporting hearing aid use in those with Mild Cognitive Impairment. We studied the feasibility of a full‐scale randomized controlled trial. Method: We conducted a pilot trial of a new intervention designed to increase uptake and adherence to hearing aid treatment. Pre COVID‐19, we randomized MCI participants to face‐to‐face interventions: the active arm is a home‐based hearing assessment and hearing aid fitting, with study audiologist and research assistant delivering motivational and practical support in 4 visits over 3 months. Participants in the control arm were referred to standard audiological care through their general practitioner without additional hearing support, and given a healthy ageing educational intervention on dementia risk factors, matched in contact with the study team. Follow‐up for both interventions was at 6 months. After the onset of COVID‐19, additional MCI participants, who had not received hearing aids, were allocated to active remote hearing support. This did not involve any face‐to‐face contact with the study team but provided hearing support remotely, with outcomes collected after 1 month. Result: Pre COVID‐19, N=36 MCI participants were randomized to the original face‐to‐face study interventions, with follow‐up measures collected at 6 months, also in a face‐to‐face session. After the onset of COVID‐19, a further N=11 received the remote hearing intervention. We will present results from these samples. The pre‐specified outcomes of the pilot include recruitment, randomization, retention, and acceptability of the interventions, with secondary outcomes including difference in usage of hearing aids between active and control arms, and cognition, mood, and social function. Conclusion: The results of this study may influence hearing care in all settings as well as dementia prevention.